2 µm mode-locked thulium-doped fiber laser using Mach–Zehnder interferometer tuning capability. (3rd May 2017) - Ahmad, H; Sharbirin, A S; Muhamad, A; Samion, M Z; Ismail, M F
Abstract: An ultrafast thulium-doped fiber laser (TDFL) with a wavelength tunable, passive mode-locked output is proposed and demonstrated. The TDFL employs a tunable Mach–Zehnder interferometer (TMZI) and a single-wall carbon nanotube (SWCNT)-based saturable absorber (SA). The TMZI provides the TDFL with a tuning range of almost 30.0 mm from 1919.4 to 1949.2 nm while at the same time maintaining the soliton output, with wavelength shifts of as small as 0.6 nm. The TDFL generates mode-locked pulses at a pump power of above 146.4 mW, and has a repetition rate of 9.1 MHz with an average minimum pulse width of 1.68 ps, as well as a maximum pulse energy and peak power value of 24.3 pJ and 13.0 W respectively. The mode-locked pulse is highly stable and has a relatively high signal-to-noise ratio value of around 56.0 dB. The use of the SWCNT-based SA is essential in generating the mode-locked pulses and the proposed laser has many potential uses in sensing and spectroscopy as well as in the generation of intense light sources for nonlinear optical applications.